Nutrient-dense snack bars from biofortified crops to enhance school children’s micronutrient intake in Tanzania - Anselm P. Moshi; Ladislaus Kasankala; Analice Kamala; Nyabasi Makori; Dyness Kejo; Hoyce Mshida; Beatrice Bachwenkizi; Malimi Kitunda; Francis Millinga; Ai Zhao; Germana H. Leyna (PLoS ONE, 2026)
Recent national surveys show that anaemia affects approximately 30–40% of school-aged children and up to 50% of adolescents in Tanzania, with prevalence exceeding 50% in some regions, underscoring the urgent need for nutrient-dense, school-appropriate food solutions. This study developed snack bars from biofortified crops and compared partially germinated and non-germinated formulations to improve the diets of school-aged children and adolescents. Germination significantly (P ≤ 0.05) increased carbohydrate, fat, fibre, and provitamin A content. Zinc content was slightly higher in the germinated bars, whereas iron content was slightly lower compared to the non-germinated formulation. Both formulations supplied 50–70% of the Recommended Dietary Allowances for carbohydrate, protein, fibre, iron and zinc iron aligning with Tanzania’s School Feeding Policy targets. Sensory testing showed higher acceptance of germinated ingredient’s snack bars for texture, colour, aroma and overall acceptability, while non-germinated bars were preferred for appearance and taste. These results demonstrate that both germinated and non-germinated biofortified snack bars can provide substantial amounts of essential nutrients in a child-friendly form. To our knowledge, this is the first study in Tanzania to develop germinated biofortified crop–based snack bars, offering a scalable, culturally acceptable approach to reducing micronutrient deficiencies among school-aged children.